Impoliteness Strategies of the Hate Comments on Twitter - Situmorang, Yuli Fransiska; Lestari, Febrika Dwi; Sinaga, Nenni Triana (LPPPI Publishing, 2024)
This study aims to determine the Impoliteness Strategies of the Hate Comments on Twitter. This study was compiled using a qualitative descriptive research method. Data from hate comments made by netizens in response to the post of the son of the Indonesian president in the comments column of the official Twitter account belonging to Gibran Rakabuming Raka and data Sources from the official Twitter account of the vice presidential candidate. The number of data in this study is 50 data. The Instrument of Collecting Data uses Observation and Documentation and the method of collecting data uses searching, reading, choosing, capturing, and printing. The data was analyzed using the Formula P=F/N x100. From the research that has been done, it was found that there is a difference in the percentage between the five types of impoliteness strategies. In the bald on record, type 4 hate comment data were found with a percentage of 8%, positive impoliteness is 6 hate comment data with a percentage of 12%, negative impoliteness is 6 hate comment data with a percentage of 12%, sarcasm or mock impoliteness is 34 hate comment data with a percentage of 68%, and withhold impoliteness is 0 hate comment data with a percentage of 0%. So, it can be concluded that the most dominant type the impoliteness strategies in the results is sarcasm or mock impoliteness with a percentage of 68% in the thesis title Impoliteness Strategies of the Hate Comments on Twitter.